Morphodynamic effects of riparian vegetation growth after stream restoration. Issue 8 (7th February 2018) - Vargas‐Luna, Andrés; Crosato, Alessandra; Anders, Niels; Hoitink, Antonius J.F.; Keesstra, Saskia D.; Uijttewaal, Wim S.J.
Abstract: The prediction of the morphological evolution of renaturalized streams is important for the success of restoration projects. Riparian vegetation is a key component of the riverine landscape and is therefore essential for the natural rehabilitation of rivers. This complicates the design of morphological interventions, since riparian vegetation is influenced by and influences the river dynamics. Morphodynamic models, useful tools for project planning, should therefore include the interaction between vegetation, water flow and sediment processes. Most restoration projects are carried out in USA and Europe, where rivers are highly intervened and where the climate is temperate and vegetation shows a clear seasonal cycle. Taking into account seasonal variations might therefore be relevant for the prediction of the river morphological adaptation. This study investigates the morphodynamic effects of riparian vegetation on a re‐meandered lowland stream in the Netherlands, the Lunterse Beek. The work includes the analysis of field data covering 5 years and numerical modelling. The results allow assessment of the performance of a modelling tool in predicting the morphological evolution of the stream and the relevance of including the seasonal variations of vegetation in the computations. After the establishment of herbaceous plants on its banks, the Lunterse Beek did not show any further changes in channel alignment. This is here attributed to the stabilizing effects of plant roots together with the small size of the stream. It is expected that the morphological restoration of similarly small streams may result in important initial morphological adaptation followed by negligible changes after full vegetation establishment. Copyright © 2018 John Wiley & Sons, Ltd. Abstract : Vegetation establishment plays a key role for channel width stabilization and for the vertical accretion of both levees and floodplains. Seasonal variations of vegetation are relevant for the morphodynamic adaptation of small streams.